2019
DOI: 10.2196/14484
|View full text |Cite|
|
Sign up to set email alerts
|

Predictors of Patients’ Loyalty Toward Doctors on Web-Based Health Communities: Cross-Sectional Study

Abstract: Background Web-based health communities provide means for patients to not only seek care but also to promote their relationship with doctors. However, little is known about the predictors of patients’ loyalty toward doctors in Web-based health communities. Objective This study aimed to investigate the predictors of patients’ loyalty toward doctors in Web-based health communities. Methods On the basis of soci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The emotional connection to the clinician is equally important in telehealth adoption. Knowing that the consultation focuses not only on the immediate health care needs but also the emotional support is critical to gaining loyalty from the patient [62]. This same issue of trust was highlighted in this study by both LLA and P&O respondents.…”
Section: Patientmentioning
confidence: 52%
“…The emotional connection to the clinician is equally important in telehealth adoption. Knowing that the consultation focuses not only on the immediate health care needs but also the emotional support is critical to gaining loyalty from the patient [62]. This same issue of trust was highlighted in this study by both LLA and P&O respondents.…”
Section: Patientmentioning
confidence: 52%
“…In a telehealth consumer study in the United States, the authors found that 66% of patients were willing to use telemedicine in 2019, but only 8% had used it previously. The authors suggest that the main reasons were the lack of familiarity with the new technology and a lack of trust in the clinician whom they have not met in person [ 61 ]. The emotional connection to the clinician is equally important in telehealth adoption.…”
Section: Discussionmentioning
confidence: 99%
“…To test the model's reliability, we calculated Cronbach's alpha and composite reliability based on the score of each item. A value of 0.5 represents acceptable reliability, and 0.7 represents good reliability [39]. To verify the convergent validity, we calculated the project load and the value of average extracted variance (AVE).…”
Section: Measurement Modelmentioning
confidence: 99%